Design and Realization of a Novel Header Compression Scheme for Ad Hoc Networks. Issue 5 (1st October 2016) - Khalid, Shahrukh; Mahboob, Athar; Azim, Choudhry Fahad; Rehman, Aqeel Ur
Abstract : IP header compression schemes offer a valuable measure for bandwidth preservation. Such schemes have been practically implemented in infrastructure‐based IP networks for point‐to‐point links. However, minimal research and practical implementation efforts have been conducted in the direction of an IP header compression strategy that can meet the peculiar requirements of multi‐hop ad hoc wireless networks. In this paper, we present a practically implemented multi‐hop IP header compression scheme using the Robust Header Compression (ROHC) protocol suite. The scheme runs on a novel identifier (ID) based networking architecture, known as an ID‐based ad hoc network (IDHOCNET). IDHOCNET additionally solves a number of bottlenecks of pure IP‐based ad hoc networks that have emerged owing to IP address auto‐configuration service, distributed naming and name resolution, and the role of an IP address as an identifier at the application layer. The proposed scheme was tested on a multi‐hop test bed. The results show that the implemented scheme has better gain and requires only O (1) ROHC contexts.